FIELD OBSERVATION OF GROUND RESPONSE DUE TO PIPE JACKING CONSTRUCTION UNDERNEATH ELECTRIC TRAIN SERVICE RAILWAY TRACK - CHE HASSAN, NUR MUHAMMAD HADRI (2021)
Tunnelling has been quite a challenge to the construction world especially when performing a tunnel excavation in developing urban areas